Imaging for assessment of sudden death risk: current role and future prospects - Suzuki, Takeki (Europace, 2016)
Sudden cardiac death (SCD) remains a major public health problem and there is an urgent need to maximize the impact of primary prevention using the implantable defibrillator. While implantable defibrillators are of utility for prevention of SCD, current methods of selecting candidates have significant shortcomings. Major advancements have occurred in the field of cardiac imaging, with significant potential to identify novel cardiac substrates for improved prediction. While assessment of the left ventricular ejection fraction remains the current major predictor, it is likely that several novel imaging markers will be incorporated into future risk stratification approaches. The goal of this review is to discuss the current status and future potential of cardiac imaging modalities to enhance risk stratification for SCD.